Cashless Society in Progress: Capturing Different Generations’ Perspectives toward External Influence in E-Wallet Usage - Widyoretno Adiani; Atik Aprianingsih; Mustika Sufiati Purwanegara (Journal of Economics, Business, and Accountancy Ventura, 2021)
The use of non-cash transaction, which is currently popular in the public, has made the topic of a cashless society discussed more often. A cashless society is a condition where people transact without using cash money so that it leads to the process from the conventional into the cashless society. In this condition, the involvement of each generation is needed. This study tries to investigate how each generation's perspective—both the younger generation and the older generation, toward the external factors, namely social influence, government support, and network externalities—affect their use of non-cash transactions in the form of e-wallet. The data were collected using focus group discussion (FGD) and a survey of 489 respondents. The data were analyzed using PLS-SEM. This research reveals how different generations have a different perspective on e-wallet and the government support has a more significant influence on the older generation than the younger generation, who tend to be more influenced by peers or family. However, both generations emphasized how the network externalities influenced the continuance usage in this service. This result implies the importance of e-wallet service providers to expand the network and collaborating with various actors to retain customers.